Effect of seed layer thickness on the Ta crystalline phase and spin Hall angle. Issue 47 (26th November 2021) - Sriram, K.; Pala, Jay; Paikaray, Bibekananda; Haldar, Arabinda; Murapaka, Chandrasekhar
Abstract : The crystalline phase of the Tantalum (Ta) deposited on the Permalloy (Py) layer strongly depends on seed Py layer thickness. Ta exhibits a phase transition from α-Ta to mixed phase (α+β)-Ta as a function of the Py thickness. Abstract : Heavy metal–ferromagnet bilayer structures have attracted great research interest for charge-to-spin interconversion. In this work, we investigated the effect of the permalloy (Py) seed layer on the tantalum (Ta) polycrystalline phase and its spin Hall angle. Interestingly, for the same deposition rates the crystalline phase of Ta deposited on the Py seed layer strongly depends on the thickness of the seed layer. We observed a phase transition from α-Ta to (α + β)-Ta while increasing the Py seed layer thickness. The observed phase transition is attributed to the strain at the interface between the Py and Ta layers. Ferromagnetic resonance-based spin pumping studies reveal that the spin-mixing conductance in the (α + β)-Ta is relatively higher as compared to the α-Ta. Spin Hall angles of α-Ta and (α + β)-Ta are obtained from the inverse spin Hall effect (ISHE) measurements. The spin Hall angle of (α + β)-Ta is estimated to be θ SH = −0.15 ± 0.009 which is relatively higher than that of the α-Ta. Our systematic results connecting the phase of Ta with the seed layer and its effect on the efficiency of spin to charge conversion might resolve ambiguities across various literature and open up new functionalities based on the growth process for emerging spintronic devices.